ARTIFICIAL RECHARGE OF GROUNDWATER: HYDROGEOLOGY AND ENGINEERING - Bouwer H. (My University, 2002)
Artificial recharge of groundwater is achieved by putting surface water in basins, furrows, ditches, or other facilities where it infiltrates into the soil and moves downward to recharge aquifers. Artificial recharge is increasingly used for short- or long-term underground storage, where it has several advantages over surface storage, and in water reuse. Artificial recharge requires permeable surface soils. Where these are not available, trenches or shafts in the unsaturated zone can be used, or water can be directly injected into aquifers through wells. To design a system for artificial recharge of groundwater, infiltration rates of the soil must be determined and the unsaturated zone between land surface and the aquifer must be checked for adequate permeability and absence of polluted areas. The aquifer should be sufficiently transmissive to avoid excessive buildup of groundwater mounds. Knowledge of these conditions requires field investigations and, if no fatal flaws are detected, test basins to predict system performance. Water-quality issues must be evaluated, especially with respect to formation of clogging layers on basin bottoms or other infiltration surfaces, and to geochemical reactions in the aquifer. Clogging layers are managed by desilting or other pretreatment of the water, and by remedial techniques in the infiltration system, such as drying, scraping, disking, ripping, or other tillage. Recharge wells should be pumped periodically to backwash clogging layers. Electronic supplementary material to this paper can be obtained by using the Springer LINK server located at http://dx.doi.org/10.1007/s10040-001-0182-4.
Keywords: ARTIFICIAL RECHARGE; GROUNDWATER MANAGEMENT; GROUNDWATER RECHARGE; UNSATURATED ZONE; WATER REUSE